Development of Antibacterial and Halochromic Textiles by Modification of Emodin from Japanese Knotweed - Martina Avbelj; Monika Horvat Zagorec; Hrvoje Petković; Marija Gorjanc; Jernej Iskra (Journal of Natural Fibers)
Emodin is a natural product with a wide range of biological activities, including antibacterial and antiviral activity against the human coronavirus NL63. Our aim was to develop antimicrobial textiles using the natural dye emodin and its derivatives and to investigate how chemical modification of emodin affects the binding properties to textiles and the antibacterial properties of the dyed textiles. Emodin was first modified by introducing different functional groups (NO2, SO3H, Br, and Cl) into the aromatic ring to obtain products with different colors. Products were used to dye various types of textiles without additional mordants. Wool and polyamide exhibited intense dye uptake, whereas cotton and polyester showed weaker affinity to emodin derivatives. The colors of dyed wool and polyamide varied, including light pink, red, violet, and almost black tones. The degree of washing fastness, pH sensitivity, and antibacterial activity of treated fabrics were also evaluated. The dyed textiles showed significant antibacterial activity against Gram-positive Staphylococcus aureus. Emodin is also present in Japanese knotweed, which is one of the most invasive alien plant species in the world and poses a major ecological and environmental problem in Europe. Therefore, this source may present environmentally friendly and sustainable source of natural dyeing agent.